The effect of qualitative exercises with bodily-kinesthetic intelligence activities on developing accuracy the skill of the undulating serves from the jump (flotter) in volleyball among first-class players for the 2022/2023 season - rda, alaa (Journal of Physical Education, 2025)
Volleyball is considered one of the most important team sports, which is practices by women and men For different age groups. Specific exercises contributed of the type of body kinetic intelligence activities clearly at the level of this sport, as it is considered the ideal, fastest, and most applicable solution, as the researcher found his problem in the lack of interest in this exercises In proportion to its importance for effectiveness, the research aims to prepare specific exercises for bodily kinetic intelligence activities , the importance of the research lies in developing the skill accuracy of the undulating serve skill of jumping (flutter) , the researcher used the experimental method with two groups, control and experimental, with pre- and post-tests .. The tests were conducted the accuracy of the skill (serving from the top (flutter)) and the research population consisted of first-class players for the 2022/2023 season, which are (6 clubs). Al-Hussein Club was chosen by a deliberate random method, and the research sample consisted of (12 players) after excluding two players (liberos) . They were divided into two equal groups and the bag was used  Statistical analysis (SPSS) to extract the results  and after presenting and discussing the results, it was concluded that there is a positive effect of specific exercises with bodily kinetic intelligence activities  on the accuracy skill of the undulating serve from jumping (flutter) with a volleyball between the pre- and post-tests for both groups , as well as between the control and experimental groups, and in favor of the experimental group and the researchers recommended the necessity of using these exercises and conducting future studies and other  on and other samples and for different skills.